Evaluation of Negative Economic‐Environmental Externalities of Overextraction of Groundwater. Issue 4 (9th October 2019) - Baniasadi, Mostafa; Zare' Mehrjordi, Mohammad Reza; Mehrabi Boshrabadi, Hossein; Mirzaei Khalilabad, Hamid Reza; Rezaei Estakhrooye, Abbas
Abstract: In recent decades, increased extraction of groundwater for human and agriculture consumption has led to a substantial drop in groundwater level in large areas of across the world. Declining groundwater levels is a serious problem in itself and has multiple economic, social, cultural, political, security‐related, and environmental externalities. The negative economic‐environmental externalities of overextraction of groundwater in the Orzouiyeh plain in the Kerman Province, Iran, were evaluated using methods such as replacement cost, production function, market prices, shadow price, and the value of the input marginal product. After evaluating externalities, the Positive Mathematical Programming method was used to evaluate different water policies to reduce the consumption of groundwater. The total economic losses due to the externalities were calculated to equal 2.8 U.S. million dollars. The damages caused by environmental externalities were calculated to equal 436.1 U.S. million dollars. The results related to the positive planning model show that the best policy among different options, such as deficit irrigation policy or combined policies, involves implementation of pressurized irrigation systems. Abstract : Article impact statement : The results show that the best policy among different options is implementation of pressurized irrigation systems.